The effect of audit committees on the earnings quality in public companies listed in Jordan - Nik Mohd Norfadzilah, Nik Mohd Rashid; Md Faruk, Abdullah; Suleman Ali, Eyal Awwad (2019)
This paper seeks to examine the effect of the characteristics of the Audit Committee (Size, Experience) on the earnings quality in the presence of corporate governance in the public companies listed on the Amman Stock Exchange (ASE). This paper provides evidence that earnings quality positively impacted by the quality of Audit Committees (AC). This study has two main objectives; the first is to conduct a review of the Jordanian laws and regulations related to audit committees in order to explore the extent of their application in public companies listed in (ASE). The second is to study the effects of audit committees on the quality of earnings in the future continuity and quality offered by these committees of financial information in these companies.